Effects of heat treatment temperatures on phase transformation, thermodynamical parameters, crystal microstructure, and electrical resistivity of NiTiV shape memory alloy - Kok, Mediha; Al-Jaf, Ahmed Omar Ali; Cirak, Z. Deniz; Qader, Ibrahim Nazem; Ozen, Ecem (Springer, 2020)
Changing physical property of NiTi shape memory alloy by adding new element and heat treatment technique has become interesting in the last decades. In this study, equiatomic NiTi alloy was doped by 1 and 5 atomic percentages of vanadium element. For each case, heat treatment was accomplished for 873, 973, 1073, and 1173 K, and its effect on phase transformation temperatures was analyzed by differential scanning calorimetry. Crystal structure and chemical compound found in XRD pattern showed the different situation for each case, e.g., TiO2 appeared in heat-treated samples, whereby the intensity of peaks varied by changing the temperature of heat treatment. In NiTi-5V alloy, each enthalpy, entropy, Gibbs free energy, and elastic energy were decreased by increasing heat treatment temperature, while grain size of the alloy extended with respect to non-heat-treated sample. Electrical resistivity of the alloys was measured as a function of temperature, which was increased by increasing vanadium composition and heat treatment temperature.
2nd International Conference on Physical Chemistry and Functional Materials (PCFM) -- JUN 25-27, 2019 -- Cappadocia, TURKEY
Keywords: Shape memory alloy; Heat treatment; NiTiV; Austenite and martensite phases; Electrical resistivity